Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The question might be trivial, but I don't understand why this minimization problem in Sobolev space $$ \min_{g}\int_{0}^{1}\left\{ f(x)-g(x)\right\}^{2} dx+\lambda\int_{0}^{1}\left\{ g^{(q)}(x)\right\} ^{2}dx $$ is equivalent to Euler equation

$$g(x)+\lambda (-1)^{q}g^{(2q)}(x)= f(x) $$ $$g^{(j)}(0)=g^{(j)}(1)=0,\ j=q,\ldots 2q-1.$$

share|cite|improve this question
up vote 3 down vote accepted

If you define the functional $$ F\big(x,g(x),g^{(q)}(x)\big) = \int_0^1 \{f(x)-g(x)\}dx + \lambda \int_0^1 \{g^{(q)}(x)\}^2 dx $$ and take test functions $h$ in the same space as the functions $g$, then \begin{multline} F\big(x,g + h, (g + h)^{(q)}\big) - F\big(x,g,g^{(q)}\big) = \\ \int_0^1\{f(x)- g(x) - h(x)\}dx + \lambda \int_0^1 \{g^{(q)}(x) + h^{(q)}(x)\}^2 dx \\ -\int_0^1\{f(x)- g(x)\}dx - \lambda \int_0^1 \{g^{(q)}(x)\}^2 dx, \end{multline} and then, the Frechet derivative is $$ D F \cdot h = 2 \lambda \int_0^1 g^{(q)}(x) h^{(q)}(x) dx - \int_0^1 h(x) dx $$ which leads me to believe you've missed a square in the first term, i.e. $$ F\big(x,g(x),g^{(q)}(x)\big) = \int_0^1 \{f(x)-g(x)\}^\color{red}{2}dx + \lambda \int_0^1 \{g^{(q)}(x)\}^2 dx $$ That being the case, the correct Frechet derivative is $$ D F \cdot h = 2 \lambda \int_0^1 g^{(q)}(x) h^{(q)}(x) dx - 2 \int_0^1 \{f(x) - g(x)\}h(x) dx $$ Integrating the first term by parts \begin{multline} D F \cdot h = 2 \lambda g^{(q)}(x) h^{(q)}(x) \Big|_0^1 \\- 2 \lambda \int_0^1 g^{(q+1)}(x) h^{(q-1)}(x) dx - 2 \int_0^1 \{f(x) - g(x)\}h(x) dx \end{multline} and so on, after $q-1$ integrations \begin{multline} D F \cdot h = 2 \lambda g^{(q)}(x) h^{(q)}(x) \Big|_0^1 - 2 \lambda g^{(q+1)}(x) h^{(q-1)}(x)\Big|_0^1 + \ldots \\ + 2 \int_0^1 \big\{\lambda (-1)^q g^{(2q)}(x) + g(x) - f(x)\big\}h(x) dx \end{multline} In order for the functional $F$ to have a critical point, the Frechet derivative $D F \cdot h = 0$ for all $h$ in the space, which leads to the Euler-Lagrange equation $$ g(x) + \lambda (-1)^q g^{(2q)}(x) = f(x) $$ with boundary conditions $$ g^{(j)}(0) = g^{(j)}(1) = 0,\quad j=q,\ldots,2q-1. $$

You only have to prove that the critical points are minima (hint: the functional is convex).

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.